The Morningside : a novel [compact disc, unabridged] - Obreht, Téa (Random House Audio, 2024)
After being expelled from their ancestral home, Silvia and her mother finally settle at the Morningside, a crumbling luxury tower in Island City where Silvia's aunt Ena serves as the superintendent. Silvia feels unmoored in her new life because her mother has been so diligently secretive about their family's past. Silvia knows almost nothing about the place where she was born and spent her early years, nor does she know why she and her mother had to leave. But in Ena there is an opening: a person willing to give the young girl glimpses into the folktales of her demolished homeland, a place of natural beauty and communal spirit that is lacking in Silvia's lonely and impoverished reality. Enchanted by Ena's stories, Silvia begins seeing the world with magical possibilities and becomes obsessed with the mysterious older woman who lives in the penthouse of the Morningside. Bezi Duras is an enigma to everyone in the building: She has her own elevator entrance and leaves only to go out at night and walk her three massive hounds, often not returning until the early morning. Silvia's mission to unravel the truth about this woman's life, and her own haunted past, may end up costing her everything.